Konsep Pendidikan Islam Berbasis Teknologi dan Pengaruhnya Terhadap Gen-Z: Telaah Atas Kitab Tarbiyah fi Zaman al-Fitan - Umam, Khaerul; Santosa, Sandi; Zakiar, Zakiar (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2025)
The role of Islamic Religious Education is crucial in shaping the character and morality of Generation Z through the effective use of technology. Islamic Religious Education aims to develop students with strong faith (iman), piety (taqwa), and ethical behavior (akhlaq) in accordance with the teachings of the Qur'an and Hadith. This study employs a library research method, with its primary reference being Tarbiyah fi Zaman al-Fitan by Ali al-Hadadi. The book emphasizes, through various quotations, the importance of children as both a blessing and a trust, and includes a Hadith that states a righteous child is one of the deeds that continue to benefit a person after death. The study discusses the integration of various forms of technology in Islamic education, including visual, audio, audiovisual media, and the internet. The findings reveal that Tarbiyah fi Zaman al-Fitan advocates for the use of technology to make learning more engaging and efficient. Key aspects highlighted in relation to technology’s influence on Generation Z include contextual understanding, character education, inclusive approaches, digital moral education, the enhancement of soft skills, and the active involvement of parents and the wider community.